2016
DOI: 10.1021/acscatal.6b01154
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Mechanism of Thioesterase-Catalyzed Macrocyclization in Erythromycin Biosynthesis

Abstract: Macrocyclic polyketides, biosynthesized by modular polyketide synthases (PKSs), have been developed successfully into generation-by-generation pharmaceuticals for numerous therapeutic areas. A great effort has been made experimentally and theoretically to elucidate the biosynthesis mechanisms, in particular for thioesterase (TE)-mediated macrocyclization, which controls the final step in the PKS biosynthesis and determines chemical structures of the final products. To obtain a better insight into the macrocycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…32 In our recent papers, the pre-reaction states (PRSs), complexes of the substrate and the active site reactant, were successfully used to understand the substrate diversity of thioesterase. 33,34 Here, the pre-reaction state (PRS) is also employed to understand the effects of R882H mutation on DNMT3A methylation. In practice, the pre-reaction state is dened as the product of the nucleophilic attack of Cys710 on cytosine.…”
Section: Introductionmentioning
confidence: 99%
“…32 In our recent papers, the pre-reaction states (PRSs), complexes of the substrate and the active site reactant, were successfully used to understand the substrate diversity of thioesterase. 33,34 Here, the pre-reaction state (PRS) is also employed to understand the effects of R882H mutation on DNMT3A methylation. In practice, the pre-reaction state is dened as the product of the nucleophilic attack of Cys710 on cytosine.…”
Section: Introductionmentioning
confidence: 99%
“…3.0Å and d (C 1 -O sub ) [?] 4.5A were defined as Pre-Reaction States (PRSs) in our previous works [25,26]. The PRS has been wildly used in structural comparisons and mutant analyses [39][40][41].…”
Section: Conformational Analyses In Amb-te and Nys-te Systemsmentioning
confidence: 99%
“…Our previous studies [26] have shown that the thioesterase-substrate system will reach Pre-Reaction States (PRSs) before the cyclization reaction occurs. In this special state, histidine and aspartic acid in the catalytic triad constitute a proton transfer chain to facilitate the deprotonation of the distal hydroxyl group of the substrate and further promote the intramolecular nucleophilic attack to obtain a tetrahedral intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of clear crystal structures, detailed theoretical approaches have been undertaken to model both cyclization and hydrolysis reactions catalyzed by DEBS TE. Chen et al used QM and MM models to investigate determinants of the reaction fate of three DEBS-like SNAC substrates [ 96 ]. Their work suggests that the reaction is mediated through an induced-fit mutual recognition between the TE enzyme and substrates.…”
Section: Thioesterases: Determinants Of Macrocylizationmentioning
confidence: 99%